2015
DOI: 10.1007/s00392-015-0899-z
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid renal tubular damage and hypoalbuminemia exacerbate cardiac prognosis in patients with chronic heart failure

Abstract: Comorbid RTD and hypoalbuminemia are frequently observed and increase the risk for extremely poor outcome in patients with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
14
1
Order By: Relevance
“…9,21,23 On the other hand, urinary tubular markers such as urinary NAG have been shown to be earlier and more sensitive indicators of AKI, suggesting that urinary tubulo-interstitial damage markers could have additional value to evaluate disease severity or association with subsequent adverse events, especially in patients with AHF. Despite most previous studies investigating the relation between tubular damage markers and clinical outcomes in only the compensated phase of HF patients in clinical trials, 9,13,20,23,28 we confirmed its prognostic value in a real-world AHF registry. Thus, we believe that admission urinary NAG could be a useful marker for further risk stratification in patients with AHF.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…9,21,23 On the other hand, urinary tubular markers such as urinary NAG have been shown to be earlier and more sensitive indicators of AKI, suggesting that urinary tubulo-interstitial damage markers could have additional value to evaluate disease severity or association with subsequent adverse events, especially in patients with AHF. Despite most previous studies investigating the relation between tubular damage markers and clinical outcomes in only the compensated phase of HF patients in clinical trials, 9,13,20,23,28 we confirmed its prognostic value in a real-world AHF registry. Thus, we believe that admission urinary NAG could be a useful marker for further risk stratification in patients with AHF.…”
Section: Discussioncontrasting
confidence: 45%
“…11,12 Among them, urinary N-acetyl-β-Dglucosamidase (NAG) is related to the severity of HF and is associated with worse clinical outcomes in patients with CHF. 9,13 Nevertheless, there is little information on the prognostic value of urinary NAG on admission, especially in relation to long-term outcomes, in hospitalised patients with AHF.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between serum albumin concentration and true GFR may be due, in part, to increased tubular creatinine secretion at lower serum albumin concentrations [27]. Also, lower serum albumin concentration may reflect renal tubular dysfunction impairing protein reabsorption from the filtrate [28], and thus may reflect tubular damage predisposing to development and progression of clinically apparent renal disease. However, this would likely have been reflected by greater urine ACR, and we found that the association of low serum albumin with ESRD events was independent of urine ACR.…”
Section: Discussionmentioning
confidence: 99%
“…Lower serum albumin concentration may reflect renal tubular dysfunction impairing protein reabsorption from the filtrate, and thus may reflect tubular damage predisposing to development and progression of clinically apparent renal disease [12,13]. There are two possible explanations for Albumin in PCG was significantly higher than those in HRI.…”
Section: Resultsmentioning
confidence: 99%